Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina J.; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication, 2022)
Modified action demonstration—dubbed motionese—has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants’ attention on the basis of movement. Results are discussed in terms of facilitative versus pedagogical learning.